Machiavelli e Castiglione: reflexos do Speculum Princeps no apogeu do renascimento - Santos, Daniel William da Silva (2009)
The present research seeks to investigate the disparity reasons that comes out between Il Principe, of Niccolò Machiavelli, and the Book Fourth by Il Cortegiano, of Baldassare Castiglione, which is about the indicated behavior for the governing class that is looking for possession and power exercise; a fact that put such books inside the same literature genres Speculum Princeps. This kind of genre also constitute a object of study through which it s possible to point out the reasons why, even having a common origin, the referred books end different perspectives for giving advices to the governing class. So, this distinction seems to be based on the different interpretations of theoretical elements among those that articulate in Speculum Princeps genre since The Old Age. Therefore, as this research intends to point out, what is created among the thoughts expressed by Machiavelli and Castiglione isn t a rupture, as its particularities would suggest, but a tension, due to the confront that these works allow to see certain contiguity